The Political Behavior of Religious Minority: A Case study of Towani Tolotang in Sidenreng Rappang Indonesia - Herman Lawelai, Hasse Jubba, Barisan,; Said, Zainal; Laila, Nur Quma (Opción, 1970)
This article aims to provide an explanation of Towani Tolotang's political behavior. The main problem raised is why this community is active in politics. By using data obtained through observation, interviews, document studies and literature studies as bases for analysis, it is found that Towani Tolotang is active in politics not only because of internal conditions that support their dynamic activities. However, it is also influenced by constitutional guarantees regarding minority rights which is also supported by the attitude of community acceptance. The conclusion of this paper confirms that minority groups such as Towani Tolotang have a variety of ways to continue to exist on the one hand by building open communication with the outside world, while they maintain the group's internal solidity on the other side.